Finite Element Scheme with H2N2 Interpolation for Multi-Term Time-Fractional Mixed Sub-Diffusion and Diffusion-Wave Equation (Advances in Applied Mathematics and Mechanics, 2024)
In this paper, two numerical schemes for the multi-term fractional mixeddiffusion and diffusion-wave equation (of order $α,$ with $0